Efeito de uma sessão de treino de força na musculação em diferentes intensidades nos níveis plasmáticos do fator neurotrófico derivado do cérebro - Marcos Borges Junior (2023)
Strength training is a widely recommended form of physical exercise for promoting healthy aging. Moreover, the use of dumbbells and machines represents an accessible strategy for safely and efficiently conducting strength training. Additionally, consistent evidence indicates that physical exercise, particularly aerobic exercise, improves memory in some way. These beneficial effects of physical exercise, especially aerobic exercise, have been associated, among other mechanisms, with increased central and circulating levels of brain-derived neurotrophic factor (BDNF). However, it remains unclear whether the intensity of strength training in weightlifting can modulate plasma levels of BDNF and, consequently, help explain the benefits induced by strength training in weightlifting. In this context, the overall objective of this study was to investigate the effect of a strength training session in weightlifting at different intensities (60% and 80% of 1 repetition maximum) on plasma concentrations of BDNF. Fourteen physically active men (41 ± 5.8 years, 174 ± 5.9 cm, 85 ± 11 kg) meeting the inclusion criteria participated in this study. The weightlifting protocol consisted of three exercises on the following machines: Bench press, Leg press 45º, and Lat pull-down. Four sets of maximal repetitions were performed at sixty (60%) and eighty (80%) percent of one repetition maximum (1 RM), with intervals of one hundred and twenty (120") seconds between sets and a cadence of one (1") second for the concentric phase and two (2") seconds for the eccentric phase. The interval between exercises was one hundred and twenty (120") seconds. Each volunteer performed both (2) protocols, with the order of execution randomized among the volunteers. The interval between the execution of the 60% 1RM protocol and the 80% 1RM protocol was seven days. Venous puncture was performed in the cubital fossa moments before, immediately after, and one hour after the exercise protocol. The concentration of BDNF was measured using the ELISA method. The results analysis showed that the strength training session at 60% of 1RM was able to increase lactate concentrations (from 1.2 to 16 mmol/L), heart rate (HR) (from 75 to 124 bpm), and rating of perceived exertion (RPE) (from 0 to 9); however, it did not alter plasma concentrations of BDNF. On the other hand, the strength training session at 80% of 1RM induced an increase in lactate concentrations (from 1.3 to 14 mmol/L), HR (from 79 to 126 bpm), and RPE (from 0 to 9.5). Furthermore, the strength training session at 80% of 1RM also altered BDNF concentrations (from 461 to 1730 pg/ml) one hour after the end of the training session. Thus, this study demonstrated that although both intensities caused physiological changes typical of strength training, such as an increase in lactate concentrations, only the 80% 1RM intensity significantly increased plasma concentrations of BDNF one hour after the end of the strength training session. This finding may provide new guidance for prescribing strength exercises in weightlifting to promote memory